Tension Recordings from Primary Bronchi in Acta2-GCaMP8.1-mVermilion Transgenic Mice - Qais Khalaf; Srijit Ghosh; Keith Thornbury (SURE Journal: (Science Undergraduate Research Experience Journal))
Contractions in smooth muscle cells are initiated by elevation of cytosolic Ca2+. It is of interest to measure Ca2+ signals in these cells. Transgenic Acta2-GCaMP8.1-mVermilion (GCaMP) mice express a genetically encoded intracellular fluorescent Ca2+ indicator in smooth muscle cells, have been developed to facilitate the study of Ca2+. However, there is a concern that the GCaMP Ca2+ indicator might buffer Ca2+ and interfere with the signals it is designed to measure. Therefore, the aim of this study was to compare tension responses in GCaMP and wild type (WT) mice to determine if the former behaved normally. Electrical field stimulation (EFS) using 2Hz pulses for 1 second, with intervals of 100 and 10 seconds, was applied to evoke transient contractions in the bronchial smooth muscle from GCaMP and WT mice. An enhancement in contraction amplitude was observed in both groups upon switching from 100s intervals to 10s. Results indicate this is due to sensitisation of the muscarinic M3 receptor (M3R)-mediated responses by recruitment of muscarinic M2 receptors (M2R). The contraction amplitudes in the GCaMP mice were smaller than in the WT, but they were of longer duration. In GCaMP, there was an increase in the baseline when the time interval changed from 100s to 10s, it could be a result of summation of contractions preventing return to baseline. Also, the degree of enhancement upon switching from 100s to 10s stimulus intervals was greater in GCaMP mice. In conclusion, marked differences in contraction were seen in GCaMP mice compared to WT, therefore results from these animals should be interpreted with caution.